Study of light propagation in dielectric loaded surface plasmon polariton waveguides - Chen, Shiyi. (2009)
Surface plasmon polaritons (SPPs), have become a hot research topic recently, due to their ability to confine and guide optical signals on subwavelength scales. Dielectric-loaded SPP waveguide (DLSPPW) is one type of SPP waveguides which has received particular interest since it is low cost, relative easy to be fabricated and provide better lateral confinement as well as low bend and propagation losses.